Green Banking in the Era of Sustainable Development: Insights from Gen Z - Nadia Meirani; Nindya Saraswati; Rinza Alesvia (Research Synergy Foundation, 2026)
The growing urgency of environmental challenges and the global Sustainable Development Goals (SDGs) has accelerated the development of green banking practices worldwide. In the context of Islamic finance, green banking is not merely an environmental initiative but is also grounded in Islamic ethical principles, particularly the concept of maqasid al-shariah and the stewardship role of humans as khalifah, which emphasize responsible financial intermediation, environmental protection, and public welfare (maslahah). This study examines how awareness and knowledge influence Generation Z’s behavioral intention to adopt Islamic green banking products, with attitude acting as a mediating variable. An explanatory (hypothesis-testing) survey design was employed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). Data were collected from [REV - blind review] 80 students at a private Islamic university in Indonesia who had completed coursework related to Islamic finance and sustainability. Measurement items were adapted from validated Theory of Planned Behavior (TPB) scales and assessed using a five-point Likert scale. The findings show that awareness and knowledge significantly influence attitude, while attitude significantly affects behavioral intention. However, the direct effects of awareness and knowledge on intention are not significant, indicating a full mediation effect of attitude. This study contributes to the Islamic green finance literature by empirically demonstrating that attitude serves as the key mediating mechanism linking awareness and knowledge to behavioral intention among Generation Z in adopting Islamic green banking.